CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

Let $$\alpha$$ and $$\beta$$ be the roots of equation $$x^2-6x-2=0$$. If $$a_n=\alpha^n-\beta^n$$, for $$n\geqslant 1$$, then the value of $$\dfrac {a_{10}-2a_8}{2a_9}$$ is equal to


A
6
loader
B
6
loader
C
3
loader
D
3
loader

Solution

The correct option is C $$3$$
$$\because \alpha, \beta $$ are the roots

$$\Rightarrow \alpha^2-6\alpha-2=0\Rightarrow \alpha^2-2=6\alpha $$

and $$\beta^2-6\beta-2=0\Rightarrow \beta^2-2=6\beta$$

Hence, $$\cfrac {a_{10}-2a_8}{2a_9}=\cfrac {\alpha^{10}-\beta^{10}-2(\alpha^{8}-\beta^{8})}{2(\alpha^{9}-\beta^{9})}$$

$$=\cfrac {\alpha^8(\alpha^2-2)-\beta^{8}(\beta^2-2)}{2(\alpha^{9}-\beta^{9})}=\cfrac {\alpha^8.6\alpha-\beta^{8}.6\beta}{2(\alpha^{9}-\beta^{9})}=\cfrac {6(\alpha^9-\beta^{9})}{2(\alpha^{9}-\beta^{9})}=3$$ 

Mathematics

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More


similar_icon
People also searched for
View More



footer-image